Dampak Teknologi pada Implikasi Sosial, Kultural, dan Keagamaan dalam Kehidupan Manusia Modern - Arivianto, Santio; Arnoldus David; Yordan Syahputra; Muhammad Syafiq Syah Nur (Moderasi: Jurnal Kajian Islam Kontemporer, 2023)
: Technology has a broad impact on life, not only on a practical level, but also on a theoretical level that influences people's thinking patterns, which ultimately influence their actions. The changes brought about by technology have not only affected urban life, but have also penetrated rural areas. Technology plays a role in expanding access to information in the form of democratization of data and information, but conversely, it also has an impact on patterns of human interaction and religious awareness. Information is usually provided by specially qualified authorities. However, technology has made authorities more open. The religious phenomena that emerge vary greatly depending on the level of exposure to technology in the environment. The emergence of electronic devices such as telephones, televisions, computers, and so on can cause us as users to be captivated by the capabilities of this technology, so that it can make us forget about our surroundings. Just imagine, almost every day we pay attention to pressing buttons on the screen which has an impact on relationships between people becoming less harmonious because they are busy with their respective gadgets.